Insulin-Producing Cells in the Drosophila Brain also Express Satiety-Inducing Cholecystokinin-Like Peptide, Drosulfakinin - Söderberg, Jeannette A.; Carlsson, Mikael A.; Nässel, Dick R. (Frontiers in Endocrinology, 2012)
Regulation of meal size and assessing the nutritional value of food are two important aspects of feeding behavior. The mechanisms that regulate these two aspects have not been fully elucidated in Drosophila. Diminished signaling with insulin-like peptides (DILPs) affects food intake in flies, but it is not clear what signal(s) mediates satiety. Here we investigate the role of DILPs and drosulfakinins (DSKs), cholecystokinin-like peptides, as satiety signals in Drosophila. We show that DSKs and DILPs are co-expressed in insulin producing cells (IPCs) of the brain. Next we analyzed the effects of diminishing DSKs or DILPs employing the Gal4-UAS system by (1) diminishing DSK-levels without directly affecting DILP-levels by targeted Dsk-RNAi, either in all DSK-producing cells (DPCs) or only in the IPCs or (2) expressing a hyperpolarizing potassium channel to inactivate either all the DPCs or only the IPCs, affecting release of both peptides. The transgenic flies were assayed for feeding and food choice, resistance to starvation, and for levels of Dilp and Dsk transcripts in brains of fed and starved animals. Diminishment of DSK in the IPCs alone is sufficient to cause defective regulation of food intake and food choice, indicating that DSK functions as a hormonal satiety signal in Drosophila. Quantification of Dsk and Dilp transcript levels reveals that knockdown of either peptide type affects the transcript levels of the other, suggesting a possible feedback regulation between the two signaling pathways. In summary, DSK and DILPs released from the IPCs regulate feeding, food choice and metabolic homeostasis in Drosophila in a coordinated fashion.